2006
DOI: 10.1063/1.2403863
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional theory with effective potential expressed as a direct mapping of the external potential: Applications to atomization energies and ionization potentials

Abstract: In this paper the authors further develop and apply the direct-mapping density functional theory to calculations of the atomization energies and ionization potentials. Single-particle orbitals are determined by solving the Kohn-Sham [Phys. Rev. A. 140, 1133 (1965)] equations with a local effective potential expressed in terms of the external potential. A two-parametric form of the effective potential for molecules is proposed and equations for optimization of the parameters are derived using the exchange-only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The potential preserves symmetry properties of the exact eigenstates and has proven to be successful for the ground state calculations of different characteristic atoms and molecules [34,37,38] and for low-lying excited states [1,2]. Therefore it is natural to try this potential for highly excited state calculations.…”
Section: Results Of Calculations and Their Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential preserves symmetry properties of the exact eigenstates and has proven to be successful for the ground state calculations of different characteristic atoms and molecules [34,37,38] and for low-lying excited states [1,2]. Therefore it is natural to try this potential for highly excited state calculations.…”
Section: Results Of Calculations and Their Discussionmentioning
confidence: 99%
“…. , 7) energies and excitation energies of the Li atom to the HF [38] and "exact" energies obtained with the most accurate configuration interaction wave function using the Hylleraas basis set [41]. It is known that high accuracy of calculation of the transition frequencies for Rydberg states of alkali metal atoms, in particular lithium, is a topical problem of theoretical methods for studying the electronic structure [44].…”
Section: Results Of Calculations and Their Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VOEP(r) is a mapping of V(r). Using symmetry principles and asymptotic conditions it was concluded that VOEP(r) is a nonlocal mapping of 2V(r). This mapping gives an approximation which in the following will be denoted by V eff and for molecules where 2V(r)=k=1NuZkδ(rboldRk), it takes the following form (see Refs. ). Veff(r)=kZk|rboldRk|+N1ZCkZk1exp(dk|rboldRk|)|rboldRk|, where Z k is the charge of the nucleus at boldRk and Z=kZk. The parameters C and d k have to be determined so that the functional E(Φ)=<Φ|H|Φ> attains its minimum value for the φi produced by this potential.…”
Section: Effective Local Potentialmentioning
confidence: 99%
“… Veff(r)=kZk|rboldRk|+N1ZCkZk1exp(dk|rboldRk|)|rboldRk|, where Z k is the charge of the nucleus at boldRk and Z=kZk. The parameters C and d k have to be determined so that the functional E(Φ)=<Φ|H|Φ> attains its minimum value for the φi produced by this potential. This method was applied successfully for the ground state calculations of atoms and molecules, excited state exchange‐only OEP calculations as well as for incorporating static correlation effects . It was also appropriate for core hole excited and ionized states .…”
Section: Effective Local Potentialmentioning
confidence: 99%